People and the City. Notes on the Identity of Siberian Cities - Sirina, Anna (project baikal, 2014)
The article reveals a complex and multicomponent identity of a Siberian city. Special attention is paid to the history of foundation of Siberian cities and ethnic identity of citizens. Like other forms of identity, ethnicity remains in the city space, while acquiring new forms of presentation, especially in the capitals of Siberian republics. Though there are regional features, referring to which we can speak about common features of formation of Siberian cities, there are no Siberian cities with similar image and history.